Hemisphere Occidental Dressé en 1720 pour l'usage particulier du Roy sur les Observations Astronimiques et Geographiques raportées la meme année dans l'Histoire et dans les memoires de l'Academie Rle. Des Sciences - L'Isle, Guillaume de, 1675-1726; DelaHaye, Jean Baptiste (L'Isle, Guillaume de 1675-1726, 1720)
18th century Copper engraving handcolored with watercolor. Full color. Mounted on muslin. Relief shown pictorially. Printed at top of map: "Hemisphere Occidental Dressé en 1720 pour l'usage particulier du Roy sur les Observations Astronimiques et Geographiques raportées la meme année dans l'Histoire et dans les memoires de l'Academie Rle. Des Sciences. Per Guillaume Del'Isle premier Geographe de Sa Majesté de la meme Academie." Printed at bottom beneath border: "A Paris Chez l'Auteur le Sieur Del'Isle sur le Quay de l'Horloge sous le Privilege de l'Academie Royale des Sciences le 15. Septembre 1724. DelaHaye Sculp." Printed along longitude 330 degrees: "Ligne de Demarcation selon la Bulle d'Alexandre VII." Depicts multiple islands throughout the South Pacific Ocean "Isles de Salomon," "Terre Australe Du S Esprit," and "Nouvelle Zelande." Illustrates the routes of several explorers and years of exploration including Magellan in 1520, Gaetan in 1542, Mendaña in 1568, Mendaña in 1595, le Maire in 1616, Quiros in 1605, Vaisseau in 1708, Vaisseau in 1710, Halley in 1700 and Tasman in 1642. The northwest region of North America is left blank extending from the border of "Quivira" up to the "Terres Arctiques." At approximately 47 degrees latitude and 185 degrees longitude a border of land is seen with the description, "Terre vue par Dom Jean de Gama en allant de la Chine a la Nouvelle Espagne." Shows some English colonies including "Caroline", "Virginie" "Mariland" and "N Anglaterre." Also depicts Greenland as connected to North America. The Great Lakes are visible though not accurately shown. Shows land where some Native American tribes reside including the Sioux and the Choctow or "Chacta." Drawn in the south Atlantic off of the coast of South America is a small ship with the description, "Jusquic y Americ Vespuce est venu par Mer." "Louisiane" takes up large portion of North America. Scale c.a. 1:27,000,000. Guillaume de L'Isle (1675-1726) was a cartographer and the Premier Geographer to the King in France beginning in 1718. His family played a significant part in the world of French cartography in the eighteenth century. At age 9, he drew his first map and at age 27 he became a member of the Académie Royale des Sciences. He studied under Jacques Cassini, acquiring knowledge in both mathematics and astronomy. Due to his academic background and his "critical approach to the maps of his predecessors," he became known as the first "scientific cartographer" (Moreland and Bannister, 132). Among his works are "Globe, map of the world and the four continents" (1700), "Atlas de Géographie" (1700-12), "Mississippi" (1701), "Carte du Mexique et de la Floride…" (c.a. 1703), "Carte de la Louisiane et du Mississippi" (1718) and posthumously, "Atlas Noveau…" (1730 and later). Following his death, his widow took up the business with a partner, Philippe Buache (Moreland and Bannister, 131-2; Tooley, "Dictionary," 395). Jean Baptiste Delahaye was an engraver. He engraved for de L'Isle in 1724 (Tooley, "Dictionary" 155). This particular map was first published in 1724 and later republished in 1745 under Buache. Wagner notes that this map in combination with his "Hémisphere Oriental" was the last map De L'Isle made of the world (Wagner, 329, entry 527). Source(s): Moreland, Carl and David Bannister. "Antique Maps: A Collector's Handbook." New York: Longman Group, Ltd., 1983. Tooley, Ronad Vere,ed. "The Mapping of America." London: Holland Press, 1985. ---. "Tooley's Dictionary of Mapmakers." Hertfordshire: Map Collector Publications Limited, 1979. Wagner, Henry R. "The Cartography of the Northwest Coast of America to the year 1800 Volume 2." Berkeley: University of California Press, 1937.